Coronaviruses SARS-CoV, MERS-CoV, and SARS-CoV-2 helicase inhibitors: a systematic review of in vitro studies - Nimer Mehyar (Elsevier, 2023)
Introduction: The recent outbreak of SARS-CoV-2 has significantly increased the need to find inhibitors that target the essential enzymes for viral replication in host cells. This systematic review was conducted to identify potential inhibitors of SARS-CoV, MERS-CoV, and SARS-CoV-2 helicases that have been tested by in vitro methods. Their inhibitory mechanisms are discussed in this review, in addition to their cytotoxic and protective properties. Methods: The databases PUBMED/MEDLINE, EMBASE, SCOPUS, and Web of Science were searched using different combinations of the keywords "helicase", "nsp13", "inhibitors", "coronaviridae", "coronaviruses", "virus replication", "replication", and "antagonists and inhibitors''. Results: A total of 6854 articles were identified. Thirty-one were included into this review. These studies reported on the inhibitory effects of 309 compounds on SARS-CoV, MERS-CoV, and SARS-CoV-2 helicase activities measured by in vitro methods. Helicase inhibitors were categorized according to the type of coronavirus and tested enzymatic activity, nature, approval, inhibition level, cytotoxicity, and viral infection protective effects. These inhibitors are classified according to the site of their interaction with coronavirus helicases into four types: zinc-binding site inhibitors, nucleic acid-binding site inhibitors, nucleotide-binding site inhibitors, and inhibitors with no clear interaction site. Conclusion: Evidence from in vitro studies suggests that helicase inhibitors have a high potential as antiviral agents. Several show good antiviral activity while maintaining moderate cytotoxicity. These inhibitors should be clinically investigated to determine their efficacy in treating coronavirus infections, particularly SARS-CoV-2.